Plasma desmosine as a biomarker in acute aortic syndrome. (14th October 2021) - Fletcher, A; Syed, M B J; Iskander, Z; Debono, S; Dweck, M R; Huang, J; Chin, C; Newby, D E; Choy, A M
Abstract: Introduction: Acute aortic syndromes (AAS) include aortic dissection, intramural haematoma and penetrating aortic ulcer, all of which are caused by aortic wall failure and associated with significant mortality. Although, treatment options currently include early surgical intervention or aggressive medical management, disease progression and devastating complications remain commonplace. Early diagnosis of AAS as well as ability to predict those at the highest risk of disease progression would represent significant progress in the care these patients receive. Desmosine is the cross-link component in the elastin molecule and is exclusively released from mature elastin breakdown, thus is a physiologically relevant biomarker of aortic elastin degradation. The aim of the study was to test the hypothesis that plasma desmosine (pDES) concentrations are elevated in AAS and has prognostic value in indentifying those at risk of significant disease progression. Method: Patients over 25 years old with radiologically confirmed acute aortic syndrome were recruited as part of a prospective observational study (NCT03647566). Demographic details, AAS sub-category, time from index acute aortic syndrome event and pDES concentrations measured by stable isotope dilution LC-MS/MS were recorded at baseline. Baseline and follow up maximal aortic diameters were measured on contrast-enhanced computed tomography (CT) and change in aortic diameter over time was calculated. Control plasma desmosine samples were obtained at a 2:1 ratio control subjects participating in the United Kingdom Aneurysm Growth Study. Data presented as mean±standard deviation or median [interquartile range]. Results: Plasma desmosine concentrations were measured in 53 patients (64 [53 to 71] years) with acute aortic syndromes and 106 control subjects (53 [44 to 60] years). In patients with AAS, pDES concentrations were almost twice those of control subjects (0.58±0.26 vs 0.27±0.07, p<0.001). In those with AAS, plasma desmosine concentrations were seen to be highest at presentation, and reduced over time from the aortic syndrome event (R=0.51, p=0.003). Plasma desmosine concentration was the only variable associated with increasing aortic diameter over time (R=0.34, p=0.014). Conclusion: Plasma desmosine concentrations are elevated in patients with AAS, peak at the time of presentation and represents a promising biomarker for early identification and risk stratification in patients with AAS. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): British Heart FoundationTenovus Scotland Major Research GrantChief Scientist Office Catalytic Grant